The long sunset - McDevitt, Jack (McDevitt, Jack. Priscilla Hutchins novels., 2018)
"Hutch has been the Academy's best pilot for decades. She's had numerous first contact encounters and even became a minor celebrity. But world politics have shifted from exploration to a growing fear that the program will run into an extraterrestrial race more advanced than humanity and war. Despite taking part in the recent scientific breakthrough that rejuvenates the human body and expands one's lifespan, Hutch finds herself as a famous interstellar pilot with little to do, until a message from an alien race arrives. The message is a piece of music from an unexplored area. Despite the fact that this alien race could pose a great danger and that this message could have taken several thousand years to travel, the program prepares the last interstellar ship for the journey. As the paranoia grows, Hutch and her crew make an early escape--but what they find at the other end of the galaxy is completely unexpected"--